PERENCANAAN STRUKTUR MUSEUM PERMAINAN ANAK TRADISIONAL DI BRINGIN KECAMATAN NGALIYAN - Rusyadi, Imron; Viantoro, Trinugroho Ardin; Kristiawan, Agung; Budirahardjo, Slamet (Universitas PGRI Semarang, 2022)
ABSTRACTThe museum is an institution entrusted by the government to store and preserve cultural heritage that is rarely known by the general public. 19 of 1995, a museum is an institution, a place for storing, maintaining, securing and utilizing material evidence of human culture as well as nature and the environment in order to support efforts to protect and preserve the nation's cultural wealth. The